Direct Oral Anticoagulants Versus Vitamin-K Antagonist After PCIs in Patients With AF: A Meta-analysis of Cardiac Ischemic Events. Issue 2 (February 2021) - Cordero, Alberto; Ferreiro, José L.; Bertomeu-González, Vicente; Rodríguez-Mañero, Moisés; Fácila, Lorenzo; Escribano, David; Sanchez-Recalde, Angel; Zuazola, Pilar; Ruiz-Nodar, Juan M.; González-Juanatey, Jose R.
Abstract : Background: Clinical trials have assessed the effect of direct oral antagonists (DOACs) in patients with atrial fibrillation (AF) after percutaneous coronary interventions (PCI). Studies were designed to test the effect on bleeding incidence, but concerns related to safety on ischemic events remain. Methods: We performed a meta-analysis with currently available studies involving DOACs versus Vitamin-K antagonist (VKA) in patients with AF after PCI. The primary endpoint was the incidence of cardiac ischemic events, including myocardial infarction and stent thrombosis. Secondary endpoints were the incidence of stroke, all-cause mortality, and major bleeding. Results: Eleven thousand twenty-three patients were included in the analysis: 5510 receiving DOACs and 5513 VKA. A total of 190 cases of myocardial infarction were registered in patients treated with DOACs and 177 in patients on VKA, and no statistical difference was noted [relative risk (RR): 1.07 95% confidence interval (CI) 0.88–1.31]. The incidence of stent thrombosis was very low with no differences between both treatment strategies (RR: 1.14 95% CI 0.76–1.71). The incidence of cardiac ischemic events was the same in patients receiving DOACs or VKA (HR 1.09 95% CI 0.91–1.30). No differences were observed in the incidence of stroke (RR: 0.86 95% CI 0.61–1.23) or mortality (RR: 1.09, 95% CI 0.90–1.31). Treatment with DOACs was associated with 34% reduction in major bleeding (RR: 0.66, 95% CI 0.54–0.81). Conclusions: Treatment with DOACs in patients with AF after a PCI do not increase the risk of cardiac ischemic events, stroke, or death and reduce the incidence of major bleeding by 34% as compared with VKA.